A Truncated 14-Amino-Acid Myelin Protein-Zero-Targeting Peptide for Fluorescence-Guided Nerve-Preserving Surgery - Nataliia Berehova; Maarten P. van Meerbeek; Samaneh Azargoshasb; Danny M. van Willigen; Leon J. Slof; Saaedeh Navaei Lavasani; Matthias N. van Oosterom; Fijs W. B. van Leeuwen; Tessa Buckle (Biomolecules, 2023)
Background: The occurrence of accidental nerve damage during surgery and the increasing application of image guidance during head-and-neck surgery have highlighted the need for molecular targeted nerve-sparing interventions. The implementation of such interventions relies on the availability of nerve-specific tracers. In this paper, we describe the development of a truncated peptide that has an optimized affinity for protein zero (P0), the most abundant protein in myelin. Methods and Materials: Further C- and N-terminal truncation was performed on the lead peptide Cy5-P0101–125. The resulting nine Cy5-labelled peptides were characterized based on their photophysical properties, P0 affinity, and in vitro staining. These characterizations were combined with evaluation of the crystal structure of P0, which resulted in the selection of the optimized tracer Cy5-P0112–125. A near-infrared Cy7-functionalized derivative (Cy7-P0112–125) was used to perform an initial evaluation of fluorescence-guided surgery in a porcine model. Results: Methodological truncation of the 26-amino-acid lead compound Cy5-P0101–125 resulted in a size reduction of 53.8% for the optimized peptide Cy5-P0112–125. The peptide design and the 1.5-fold affinity gain obtained after truncation could be linked to interactions observed in the crystal structure of the extracellular portion of P0. The near-infrared analogue Cy7-P0112–125 supported nerve illumination during fluorescence-guided surgery in the head-and-neck region in a porcine model. Conclusions: Methodological truncation yielded a second-generation P0-specific peptide. Initial surgical evaluation suggests that the peptide can support molecular targeted nerve imaging.